2022
DOI: 10.3390/mps5010016
|View full text |Cite
|
Sign up to set email alerts
|

Development of Primary Monolayer Cell Model and Organotypic Model of Uterine Leiomyoma

Abstract: Cellular technologies are one of the most promising areas of biomedicine, which is based on the isolation of cells of various types, followed by their cultivation and use, or the use of their metabolic products, for medical purposes. Today, a significant part of biomedical research is carried out in vitro. On the other hand, organotypic culture can be used as a powerful model system and can complement cell culture and in vivo studies in different biomedical applications. Uterine leiomyoma (UL) is a very common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Primary UF cell lines were obtained previously after myomectomy in the D.O. Ott Research Institute of Obstetrics, Gynecology and Reproductology (Saint Petersburg, Russia) and maintained as described earlier [31,68].…”
Section: Cell Linesmentioning
confidence: 99%
“…Primary UF cell lines were obtained previously after myomectomy in the D.O. Ott Research Institute of Obstetrics, Gynecology and Reproductology (Saint Petersburg, Russia) and maintained as described earlier [31,68].…”
Section: Cell Linesmentioning
confidence: 99%
“…Primary UL cells were isolated from UL nodes after myomectomy at the D.O. Ott Research Institute of Obstetrics, Gynecology and Reproductology (Saint-Petersburg, Russia), as previously reported [22,23]. The UL cells were cultured in AmnioMAX C-100 Complete Medium (Thermo Fisher Scientific, Carlsbad, CA, USA) and transfection experiments were held in DMEM-F12 (Thermo Fisher Scientific) supplemented with 10% FBS (Thermo Fisher Scientific) and 0.3% gentamicin.…”
Section: Cell Linesmentioning
confidence: 99%
“…Suicide gene therapy based on HSV-TK transgene and GCV metabolism specificities is widely used to selectively kill tumor cells [ 51 ]. To assess the potential use of the peptide DNA delivery vehicles studied here, we transferred HSV-TK genes into primary uterine leiomyoma cells obtained after myomectomy from women with the disease [ 52 ]. Our previous studies demonstrated that up to 73% of UL cells are αvβ3-positive [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Primary UL cells were isolated from myomatous nodes after hysterectomy was carried out in the D.O. Ott Research Institute of Obstetrics, Gynecology and Reproductology (Saint-Petersburg, Russia), as described previously [ 52 ]. Briefly, the UL cells were propagated in AmnioMAX C-100 Complete Medium (Thermo Fisher Scientific, Carlsbad, CA, USA) supplemented with 10% FBS (Thermo Fisher Scientific) and 0.3% gentamicin.…”
Section: Methodsmentioning
confidence: 99%